In vitro enzymatic degradation of the PTMC/cross-linked PEGDA blends - Li, Wei; Lin, Meina; Wang, Chenchao; Lu, Yongping; Sui, Yu; Ni, Xiang; Guo, Jing; Jiang, Miao; Yang, Liqun; Cui, Hong (Frontiers in Bioengineering and Biotechnology, 2023)
The blends of poly(trimethylene carbonate) (PTMC) and cross-linked poly(ethylene glycol) diacrylate (PEGDA) were prepared by mixing photoactive PEGDA and PTMC and subsequently photopolymerizing the mixture with UV light. The physical properties and in vitro enzymatic degradation of the resultant PTMC/cross-linked PEGDA blends were investigated. The results showed that the gel fraction of PTMC/cross-linked PEGDA blends increased while the swelling degree decreased with the content of PEGDA dosage. The results of in vitro enzymatic degradation confirmed that the degradation of PTMC/cross-linked PEGDA blends in the lipase solution occurred under the surface erosion mechanism, and the introduction of the UV cross-linked PEGDA significantly improved the resistance to lipase erosion of PTMC; the higher the cross-linking degree, the lower the mass loss. The results indicated that the blends/cross-linking via PEGDA is a simple and effective strategy to tailor the degradation rate of PTMC.